Analysis of Construction Delay Factors: A Case Study of Ghiring Rural Municipality, Nepal (OODBODHAN, 2025)
This study investigates the primary causes and effects of construction delays in public infrastructure projects executed under National Competitive Bidding (NCB) in Ghiring Rural Municipality, Nepal, from fiscal years 2074/75 to 2080/81. The objective was to identify and prioritize delay factors and their consequences on project performance using a quantitative, stakeholder-centered approach. Data were collected through structured surveys administered to 70 respondents, including contractors, consultants, engineers, and municipal officials. The Relative Importance Index (RII) was applied to rank delay causes and effects from the perspectives of all stakeholders. The analysis identified 14 critical delay factors, with the most significant being shortage of necessary equipment (RII = 0.974), low bidding of contracts (RII = 0.971), material unavailability on site (RII = 0.966), and ineffective contractor planning and supervision (RII = 0.963). Consultant-related issues—such as delayed inspections, poor communication, and incomplete feasibility studies—also scored high across all groups. Seven dominant delay effects were identified, including project time overruns, increased costs, service stagnation, and accumulation of interest on project capital. The findings highlight a systemic performance gap across all actors in the project lifecycle. These insights provide an evidence base for targeted interventions aimed at minimizing future delays in rural infrastructure development.